Comparative study on litter production and nutrient return to soil in Tarai and Hill Sal (Shorea robusta Gaertn.) forests of eastern Nepal - Bhattarai, K. P.; Mandal, T. N. (Banko Janakari, 2018)
Litter production and nutrient return to soil through litter fall is important pathway for the regulation of nutrient cycling and primary production of the forest. Litter fall dynamics is generally influenced by phenology of tree species, seasons and altitude of the forest stand. As most of the information on litter production are from temperate and dry tropical region. A comparative study on litter production and nutrient return were conducted in Terai Sal forest (TSF) and Hill Sal forest (HSF) located in moist tropical region of eastern Nepal. Litter samples were collected from the litter traps (1m × 1m size) placed randomly in the forest. Collection was done at two months interval for one year. Annual litterfall in TSF (8.82 Mg ha-1y-1) was significantly (p < 0.001) higher than in HSF (7.18 Mg ha-1y-1).There was distinct seasonality in litter production. In TSF and HSF, litterfall was maximum in the summer (6.57 Mg ha-1 and 5.05 Mg ha-1, respectively) and minimum in winter season (0.86 Mg ha-1 and 0.72 Mg ha-1, respectively). Amount of nutrient return to forest soil through litter fall (kg ha-1 y-1) was higher in TSF (72.44 N, 6.80 P and 33.23 K) than HSF (54.31 N, 4.84 P and 22.23 K). The difference in litter production between these two forests was influenced by the phenology of dominant tree species, variation in altitude and seasons. Nutrient return through litter fall is a great input of nutrients in soil which is required for production process. Thus, litter constitutes a significant role in forest management. Banko Janakari A Journal of Forestry Information for Nepal Vol. 28, No. 1, 2018, page: 11-19